Preliminary Studies on the Steam Explosion Pretreatment of the Oil Palm Stem - Mansor, Halimathon; Sudo, K.; Ishihara, M. (1990)
Steam explosion was found to be an effective method of improving the enzymatic hydrolysis of cellulose in the oil palm stem. The pretreatment also caused the degradation of hemicelluloses and Tendered them water-soluble. By aqueous extraction of the exploded material 23-31 % hemicelulosa with xylose contents up to 83% after acid hydrolysis coultd be recovered. This paper also discusses some m0rphological changes which occurred in the pretreatment.